STUDI TENTANG BENTUK, MOTIF, DAN FUNGSI ANYAMAN KAMPIA DI NAGARI MATUA MUDIAK KECAMATAN MATUR KABUPATEN AGAM - Ayang Mulya Putra; Ernis Ernis (Serupa The Journal of Art Education, 2021)
The writing of this scientific final paper intends to obtain empirical data based on the description of the form, motif and function of Kampia weaving in Nagari Matua Mudiak, Matur District. By going through qualitative type research along with an inductive approach so as to provide accuracy to the data. In terms of form, the results can be seen in the form of a Tas Kampia Jabak, Dompet Terawang, and Kampia Sandangan. Through by the form classification it can be seen the forms of motifs and the functions that exist in Kampia weaving.Kata kunci: kampia, webbing Matua Mudiak.